How inflammation blunts innate immunity in aging - Goldberg, Emily L. (Interdiscip Top Gerontol Geriatr, 2020)
The collective loss of immune protection during aging leads to poor vaccine responses and an increased severity of infection for the elderly. Here we review our current understanding of effects of aging on the cellular and molecular dysregulation of innate immune cells as well as the relevant tissue milieu which influences their functions. The innate immune system is composed of multiple cell types which provide distinct and essential roles in tissue surveillance and antigen presentation as well as early responses to infection or injury. Functional defects that arise during aging lead to a reduced dynamic range of responsiveness, altered cytokine dynamics, and impaired tissue repair. Heightened inflammation influences both the dysregulation of innate immune responses as well as surrounding tissue microenvironments which have a critical role in development of a functional immune response. In particular, age-related physical and inflammatory changes in the skin, lung, lymph nodes, and adipose tissue reflect disrupted architecture and spatial organization contributing to diminished immune responsiveness. Underlying mechanisms include altered transcriptional programming and dysregulation of critical innate immune signaling cascades. Further, we identify signaling functions of bioactive lipid mediators which address chronic inflammation and may contribute to the resolution of inflammation to improve innate immunity during aging.